Visual Storytelling in Food Photography: An Aesthetic and Narrative Analysis of Pour-Over Coffee Images - Afif, Fuadi; Hermawan, Hary; Anwari, Hamdan; Damasdino, Fian; Fithriya, Dwi Nur Laela (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2025)
Food photography has developed into a medium that transcends documentation, functioning as a form of aesthetic expression and cultural storytelling. This study analyzes a series of eight photographs depicting the pour-over brewing process of single-origin Kenya Gichathaini coffee. Using a qualitative visual analysis approach, the study integrates technical aspects of photography—composition, lighting, color, and depth of field—with narrative frameworks that shape viewers’ sensory experiences. The photographs were taken with a Fujifilm X-M1 camera and a TTArtisan 23mm f/1.4 lens, using continuous LED lighting with a softbox positioned at 8 o’clock. Each image was examined through established compositional rules such as the rule of thirds, golden ratio, and leading lines, alongside principles of soft directional lighting and negative space. Findings reveal that visual coherence, strategic use of composition, and controlled lighting work together to create a compelling narrative arc: from product identity, materiality of coffee beans, human interaction, brewing accuracy, process dynamics, transformation through blooming, contextual setup, and the final cup. This study highlights how food photography serves as both an aesthetic practice and a cultural text, contributing to the broader discourse of visual gastronomy. The implications extend to photographers, academics, and gastronomy practitioners seeking to craft food images that are not only visually appealing but also narratively meaningful.